Efisiensi Teknis Usahatani Kedelai (Glicine Max L) di Kabupaten Banyumas: Indonesia - Ulfah Nurdiani; Kunandar Prasetyo (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2023)
Soybean is a strategic food in Indonesia. National soybean consumption continues to increase every year. However, there is still a large gap between national soybean production and consumption. This study aims to analyze the factors that influence soybean production, the level of technical efficiency and the sources of technical inefficiency in soybean farming in Banyumas Regency. The number of samples was 45 farmers from 3 sub-districts, namely Kebasen, Sokaraja and Kedungbanteng. Data analysis uses frontier stochastic production function analysis to analyze the factors that influence the technical efficiency of soybean farming. The estimation results of the Stochastic Frontier Production Model show that the variables that have a significant effect on soybean production are land area, number of seeds, and pesticides. The level of achievement of technical efficiency of soybean farming is 0.728. This shows that rice farming in Banyumas Regency is already efficient. Factors that significantly influence the technical inefficiency of soybean farming in Banyumas Regency is the age of the farmer